2021
DOI: 10.3390/geomatics1040027
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Similarity of Deforestation Patterns in Time and Space across Differences in Resolution

Abstract: This article demonstrated an easily applicable method for measuring the similarity between a pair of point patterns, which applies to spatial or temporal data sets. Such a measurement was performed using similarity-based pattern analysis as an alternative to conventional approaches, which typically utilize straightforward point-to-point matching. Using our approach, in each point data set, two geometric features (i.e., the distance and angle from the centroid) were calculated and represented as probability den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…(CDFs) of various geometric features across thresholds ranging from 50 to 130. This a ysis, as reported in [25], confirmed that a threshold near 100 was optimal.…”
Section: Vegetation Cover Change Detectionsupporting
confidence: 82%
See 4 more Smart Citations
“…(CDFs) of various geometric features across thresholds ranging from 50 to 130. This a ysis, as reported in [25], confirmed that a threshold near 100 was optimal.…”
Section: Vegetation Cover Change Detectionsupporting
confidence: 82%
“…The study conducted a sensitivity and sensibility analysis utilizing probability density functions (PDFs) and cumulative distribution functions (CDFs) of various geometric features across thresholds ranging from 50 to 130. This analysis, as reported in [25], confirmed that a threshold near 100 was optimal.…”
Section: Vegetation Cover Change Detectionsupporting
confidence: 80%
See 3 more Smart Citations